A new perspective to evaluate CLOSE protocol by coronary CT angiography including the evaluation of left atrial wall thickness. (4th February 2022) - Boussoussou, M; Szilveszter, B; Vattay, B; Kolossvary, M; Vecsey-Nagy, M; Sallo, Z; Maurovich-Horvat, P; Merkely, B; Geller, L; Szegedi, N
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This study was supported by the National Research, Development and Innovation Office of Hungary (NKFIA; NVKP_16-1-2016-0017 National Heart Program). The research was supported by the Thematic Excellence Programme (Tématerületi Kiválósági Program, 2020-4.1.1.-TKP2020) of the Ministry for Innovation and Technology in Hungary, within the framework of the Therapeutic Development and Bioimaging programmes of the Semmelweis University. The project was supported by the KH-17 Programme of the National Research, Development and Innovation Office of the Ministry of Innovation and Technology in Hungary (NKFIH). Bálint Szilveszter MD PhD was supported by the ÚNKP-20-4-II New National Excellence Program of the Ministry for Innovation and Technology from the source of the National research, Development and Innovation fund. M. Boussoussou and B. Vattay were supported by the "NTP-NFTÖ" (Nemzeti Tehetség Program, Nemzet Fiatal Tehetségeiért Ösztöndíj) program of the Ministry of Human Capacities in Hungary (EMMI) and by the EFOP-3.6.3-VEKOP-16-2017-00009. Introduction: The CLOSE protocol is a novel contact-force guided technique for enclosing pulmonary veins in patients with atrial fibrillation (AF). We sought to determine whether left atrial (LA) wall thickness (LAWT) and pulmonary vein (PV) dimensions as assessed by coronary CT angiography (CTA) could influence the efficacy of successful first-pass isolation using the CLOSE protocol. Methods: In a single center, prospective study we enrolled 94 patients with symptomatic, drug-refractory AF who underwent pre-ablation left atrial CTA and initial radiofrequency catheter ablation between 2019.01-2020.09. The LA was divided into 11 regions when assessing LAWT. Additionally, the diameter and area of the PV orifices were obtained. First pass isolation was recorded separately for the right and left PVs. After the first-pass ablation circles were ready, additional ablations were applied in those cases where first pass isolation was not achieved, to reach complete PV isolation. Predictors of successful first pass isolation were determined using logistic regression models that included anthropometrical, echocardiographic and CTA derived parameters. Results: A total of 94 patients were included in the analysis with mean CHA2DS2-VASc score of 2.1 ± 1.5 (mean age 62.4 ± 12.6 years, 39.5% female). 61.7 % were paroxysmal, 38.3 were persistent AF patients. First-pass isolation rate was 76%, 71% and 54%, for the right PVs, left PVs and all four PVs, respectively. No difference was found regarding comorbidities and imaging parameters between those with and without first-pass isolation. LAWT (mean of all 11 regions or separately) had no effect on the procedural outcome (all p >0.05). Mean procedure times were 81.2 ± 19.3 minutes. Complete isolation of all four PVs was achieved in 100% of patients. Out of all assessed parameters, only RSPV diameter was associated with right sided successful PVI on first pass isolation (p = 0.04, OR 1.01). Conclusion: The use of CLOSE protocol in AF patients resulted in high periprocedural success rate in terms of first pass isolation, independently from the thickness of the LA wall. RSPV diameter could influence the results of first pass isolation.